Developmental trends in requests rendered by EFL speakers in Poland - Szczepaniak-Kozak, Anna (Państwowa Wyższa Szkoła Zawodowa w Koninie, 2017)
The primary concern in this paper is with developmental issues in EFL learners’ interlanguage (acquisitional) pragmatics (ILP) in Poland, operationalized as rendering requests. It discusses selected findings of a longitudinal study lasting for three years and relying on data collected among 57 EFL learners by means of a written discourse completion task of an open response format. The data collected in the third year (Y3) of the study indicate that even if these EFL students make correct judgments of sociopragmatic factors involved in a particular scenario, selecting appropriate pragmalinguistic forms remains problematic to them. This is hypothesized to be a result of transfer from their mother tongue and/or lack of corrective instruction. However, positive developments towards the target language pragmatic competence were also observed, that is a greater diversification of the requestive strategies used, fewer grounders and a higher frequency of certain internal mitigation features.
Keywords: interlanguage pragmatic competence; Polish learners of English as a foreign language; DCT; requests